The International Society for the History of Medicine Begins the Celebration of Its 100th Anniversary in Latvia - Juris Salaks; Marika Garnizone (Acta Medico-Historica Rigensia, 2021)
In August 2020, Riga became the world’s capital of the history of medi- cine, hosting the 47th Congress of the International Society for the History of Medicine (ISHM). The Congress was organised by the Latvian Society for the History of Medicine in cooperation with Rīga Stradiņš University and Pauls Stradiņš Museum of the History of Medicine.